Application of Orem’s theory on wounds: an integrative review - Melo, Larissa Houly de Almeida; Bernardo, Thaís Honório Lins; Macedo, Jane Keyla Souza dos Santos; Francisco, Leilane Camila Ferreira de Lima; Barros, Alice Correia (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize the scientific production on the application of Orem’s self-care theory in the scope of wounds. Method: Integrative literature review with the available articles that highlight the theme. The following informational resources were used: VHL, CINAHL, Scopus, Cochrane, PubMed and SciELO. The following descriptors were listed: Self Care, Nursing Theory, Wound and Ulcer, in their English and Portuguese versions. The final sample consisted of 10 publications. Data were collected using a validated tool. Evaluation and data synthesis were produced through description and simple statistical evaluations. Results: The analyzed researches were developed in four countries; English language was predominant; publications began in 2004. The theory was applied in nursing care systematization, as a teaching strategy for self-care and as a theoretical framework. The articles linked the theory to diabetic foot, venous ulcer, leg/lower limb ulcers (no specification of type), burns and pressure injury. Conclusion: Orem’s theory was applied to a variety of individuals and contexts, its applicability within the scope of wounds is something concrete, regardless of the type of injury.